Effect of chronic lithium chloride on membrane adenosine triphosphatases in certain postural muscles of rats - Adipudi, Vijayalakshmi; Reddy, V.Krishna (European journal of pharmacology, 1994)
Lithium has been extensively used as an antidepressant in the treatment of manic depressive disorders requiring chronic administration. Here, we report a study of the effect of long-term lithium treatment on the activities of membrane adenosine triphosphatases (ATPases) in certain postural muscles of rat. Specifically, Ca 2+-ATPase, Na +,K +-ATPase and Mg 2+-ATPase activities were measured in the soleus, extensor digitorum longus and plantaris muscles following 6 weeks of treatment with LiCl. Increases were observed in the Na +,K +-ATPase activity whereas the Mg 2+-ATPase activity decreased with prolonged LiCl treatment. The most pronounced effect was a highly significant ( P<0.001) increase in the mitochondrial Ca 2+-ATPase and Na +,K +-ATPase activity to almost 50–100% above the control. The increases in the mitochondrial Ca 2+-ATPase activity of extensor digitorum longus and plantaris were 70% and 100%, respectively. The corresponding increases in the Na +,K +-ATPase activity were 127%, 99% and 87% for soleus, extensor digitorum longus and plantaris, respectively. Irrespective of the differences in the fiber pattern and physiological function, all three muscles responded in a similar way to Li +. The changes in the membrane ATPases reflect a deranged ATP turnover, thus affecting the overall energy state of the animal. Based on these results, we hypothesize that Li + produces its effects by interfering with cation transport processes. Since Li + affects the neural excitability of the cell it is suggested that the stimulation of the ATPases may be important in the psychotropic properties of the ion.